What is the International Monetary Fund?. (Pamphlet Series; Pamphlet Series, No., 2006)
An introductory guide to the IMF, its history, and its role in the international financial system. Explains for a general audience the IMF's lending policies, how decisions are made, and where the money comes from. Gives details of the structure of the IMF, its increasing transparency, how it provides technical assistance to member countries, its role in crisis prevention, and how it is helping the world's poorest countries. Revised in August 2006.